In vivo activity and pharmacodynamics of amoxicillin in combination with fosfomycin in fibrin clots infected with highly penicillin-resistant Streptococcus pneumoniae. - Chavanet, P (1996)
Using a clinical pneumococcal strain for which MICs were 4, 2, and 32 mg/liter for penicillin, amoxicillin, and fosfomycin, respectively, we studied the efficacies of these antibiotics alone and their combinations in the treatment of prolonged (48-h) experimental fibrin clot infection in rabbits. Treatments were as follows: amoxicillin IV at 20 mg/kg of body weight in one dose (Amo20), 50 mg/kg in one dose (Amo50), or two doses 6 h apart (Amo20 x 2 and Amo50 x 2); fosfomycin IV at a fixed dose of 50 mg/kg in one dose (Fos50) or two divided doses 6 h apart (Fos50 x 2); or the combinations of amoxicillin and fosfomycin with the same schedules. Maximum concentrations in clots were 2.03 +/- 1.02 and 2.13 +/- 0.33 mg/liter for Amo20 regimens, 3.7 +/- 1.9 and 4 +/- 1.3 mg/liter for Amo50 regimens, and 24 +/- 7 and 40 +/- 8 mg/liter for fosfomycin regimens, respectively. The mean half-lives of elimination from clots were between 2 and 3 h for amoxicillin regimens and between 5 and 7 h for fosfomycin. We observed the highest bacterial reductions (log10 CFU/gram) for Amo50 in two divided doses with or without fosfomycin. A significantly higher bacterial reduction than that with each monotherapy was observed when Amo20 was combined with fosfomycin in either one dose or two doses 6 h apart (0.16 +/- 0.8 and 1.64 +/- 1.6 log10 CFU/g for Amo20 in one and two doses, respectively, and 0.93 +/- 0.81 and 0.61 +/- 0.56 log10 CFU/g for fosfomycin in one and two doses, respectively, versus 3.46 +/- 1.26 and 3.16 +/- 1.31 log10 CFU/g for Amo20 plus fosfomycin in one and two doses, respectively [P < 0.001]). A time-dependent effect was observed with amoxicillin regimens. The time of regrowth was significantly delayed when amoxicillin was combined with fosfomycin. By using a multivariate analysis, we demonstrated that the most important parameter correlated to efficacy of the combination amoxicillin-fosfomycin was the length of the period during which the concentration of amoxicillin remained above the MIC. We demonstrated that the in vivo efficacy of the combination of amoxicillin and fosfomycin gave higher antibacterial effect than each monotherapy.